Implantable Energy Harvesters: Implantable Cardiac Kirigami‐Inspired Lead‐Based Energy Harvester Fabricated by Enhanced Piezoelectric Composite Film (Adv. Healthcare Mater. 8/2021). Issue 8 (21st April 2021) - Xu, Zhe; Jin, Congran; Cabe, Andrew; Escobedo, Danny; Gruslova, Aleksandra; Jenney, Scott; Closson, Andrew B.; Dong, Lin; Chen, Zi; Feldman, Marc D.; Zhang, John X. J.
Abstract : Implantable energy harvesters offer a promising solution to overcome the power challenge encountered by most biomedical devices. In article number 2002100 Zi Chen, Marc D. Feldman, John X. J. Zhang, and co‐workers, prudently take advantage of both a metamaterial and a piezoelectric composite material, to develop a novel, flexible Kirigamiinspired energy harvester that can convert the pacemaker leads bending energy to electrical power. This technology realizes energy sustainability for implantable biomedical devices.